Raised serum alkaline phosphatase and aspartate transaminase levels in two rheumatoid patients treated with sulphasalazine. Issue 11 (November 1985) - Farr, M; Symmons, D P; Bacon, P A
Abstract : Hepatotoxicity is a rare complication of sulphasalazine therapy in ulcerative colitis. This report describes two rheumatoid patients in whom raised serum levels of liver enzymes occurred soon after starting sulphasalazine treatment for their arthritis. In both cases the serum enzyme levels returned to normal after stopping the drug. Drug-induced hepatotoxicity should be considered in patients with rheumatoid arthritis (RA) who develop raised serum levels of liver enzymes while taking sulphasalazine.